Phenotyping Healthcare Use 2–3 Decades Before the First Multiple Sclerosis Demyelinating Event - Helen Tremlett; Karl Everett; Colleen J. Maxwell; Feng Zhu; Ayesha Asaf; Ping Li; Kyla A. McKay; Yinshan Zhao; Ruth Ann Marrie (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Phenotype hospital, physician, and emergency department (ED) visits by diagnoses and specialty up to 29 years pre‐multiple sclerosis (MS) onset versus a matched population without MS. Methods We identified people with MS (PwMS) using population‐based administrative data from Ontario, Canada (1991–2020). The first MS/demyelinating diagnostic code defined MS onset (the index date). Annual rates of healthcare use (hospital, physician, ED) by primary diagnosis (chapter‐level) and physician specialty pre‐index were compared between PwMS and up to 5 matched population comparators using overdispersed‐Poisson regression. Results Up to 35,018 PwMS and 136,007 population comparators were included. Consistently elevated yearly physician visit rate ratios (RRs) were observed 28 years pre‐index for: mental‐health (RR > 1.29) and ill‐defined signs/symptoms (RR > 1.15), 24 years for: nervous (RR > 1.47), musculoskeletal (RR > 1.21), injury, and respiratory‐related issues (RR > 1.07), and 22 years for digestive‐system (RR > 1.18). The magnitude increased as the index date approached, peaking the year pre‐index for physician, hospital, and ED visit RRs for: nervous‐system (range: 12.06–17.13); ill‐defined signs/symptoms (range: 3.51–5.45), mental‐health (range: 2.13–2.70), musculoskeletal (range: 1.84–2.96), injury (range: 1.58–2.27), digestive‐system (range: 1.49–1.78) and respiratory‐system (range: 1.37–2.06). By specialty, yearly visit RRs for primary care were > 1.08 for 28 years pre‐index, internal medicine exceeded 1.19 for 25 years, and psychiatry and neurology > 1.52 for 24 years pre‐index. Interpretation Higher healthcare use was evident for over two decades before the first demyelinating event. Mental‐related, ill‐defined signs/symptoms and primary care visits were consistently elevated the longest (28 years pre‐index), followed by nervous‐system, musculoskeletal, injury, respiratory‐related, and digestive‐system (22–24 years pre‐index). Health‐related phenotypical differences appear early in the MS disease process.